Uma Heurística Baseada em Programação Dinâmica para o Problema de Corte Bidimensional Guilhotinado 2-Estágios - Assis, N. S. [UNESP]; Rangel, S. [UNESP] (Sociedade Brasileira de Matemática Aplicada e Computacional - SBMAC, 2022)
Cutting and packing problems are part of the production planning process in many industries (e.g. paper, glass, furniture). In some furniture industries, large rectangular objects have to be cut into smaller rectangles and there is a limited storage space for work in process. In this case there is interest in solving the constrained two-dimensional two-stages guillotine cutting problem (PCBG-2est). Several authors applied dynamic programming algorithms for solving the unconstrained two-dimensional cutting problem. However, for the constrained case this technique still presents some challenges due to the size of the state space. We propose a heuristic based on the two-step method of Gilmore and Gomory for the constrained PCBG-2est considering special constraints associated with the cutting equipment. The results of a computational study with three sets of instances show the efficiency of the proposal. In particular, for instances that are similar to the furniture industry, solutions were obtained with an average maximum gap of 4.4%.

Problemas de corte e empacotamento fazem parte do processo de planejamento da produção em muitas indústrias (e.g. papel, vidro, móveis). Em algumas dessas indústrias, um objeto retangular grande deve ser cortado em itens retangulares menores e existe uma capacidade limitada para o estoque dos itens. Nesse contexto, surge o problema de corte bidimensional guilhotinado 2-estágios restrito (PCBG-2est). Alguns autores têm proposto algoritmos de programação dinâmica para resolver o problema no caso irrestrito. Para o caso restrito essa técnica ainda apresenta alguns desafios devido à dimensão do espaço de estados. Nesse artigo propõem-se duas heurísticas baseadas em programação dinâmica e no método de Gilmore e Gomory para resolver o PCBG-2est restrito. São apresentados resultados do estudo computacional realizado com três conjuntos de instâncias que mostram a eficiência da proposta. Em particular, para instâncias similares às encontradas na indústria moveleira foram obtidas soluções com gap máximo médio de 4.4%.
Keywords: Two-dimensional two-stages guillotine cutting problem; constrained problem; dynamic programming; heuristic; Problema de corte bidimensional guilhotinado 2-estágios; problema restrito; programação dinâmica; heurística